Expression of CPEB4 in Human Glioma and Its Correlations With Prognosis. Issue 27 (July 2015) - Hu, Wanming; Yang, Yuanzhong; Xi, Shaoyan; Sai, Ke; Su, Dongfang; Zhang, Xinke; Lin, Suxia; Zeng, Jing; Li., Bo
<x xml:space="preserve">Abstract</x> Abstract CPEB4 plays an important role in cancer progression. However, the clinicopathological significance of CPEB4 expression to glioma and its expression levels in glioma tissues and cell lines are unknown. The present study investigated the potential prognostic value of CPEB4 for human glioma. Immunohistochemistry (IHC) was performed to examine the dynamics of CPEB4 expression in glioma and nonneoplastic brain tissues, and the expression of CPEB4 in cell lines and freshly prepared tissue samples was measured using Western blotting and real-time PCR. CPEB4 was highly expressed at the mRNA and protein levels in 4 glioma cell lines and in 4 freshly prepared glioma tissues. Immunohistochemical analysis demonstrated that CPEB4 expression in glioma tissue was higher than that in corresponding nonneoplastic brain tissue (P < 0.01). This high expression level was further increased in high-grade gliomas, and the CPEB4 expression level correlated with the WHO classification (r = 0.774, P < 0.01). Moreover, the overall survival of glioma patients displaying high CPEB4 protein expression (P < 0.01) was clearly lower than that of those displaying low CPEB4 expression, and the high CPEB4 expression indicated a poorer survival in high-grade glioma patients (P < 0.01). Our study suggests that CPEB4 is significantly expressed in human glioma and that the upregulation of CPEB4 protein is significantly associated with advanced WHO grade. CPEB4 may serve as a highly sensitive prognostic indicator for glioma patients.